2022
DOI: 10.1111/jfb.15131
|View full text |Cite
|
Sign up to set email alerts
|

Slower growth of farmed eels stocked into rivers with higher wild eel density

Abstract: Farmed anguillid eels are frequently stocked into natural fresh waters to enhance eel resources, but little is known about what happens to these eels or their interactions with wild eels after stocking. A recent study observed a depressed survival and growth rate of farmed Japanese eels when they were reared with wild eels, which indicated that wild eels might interfere with the survival and growth of farmed-and-stocked eels through intraspecific competition. To contribute to improving eel stocking efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To evaluate the possible effects of wild eels on farmed eels that were stocked in natural water bodies, Wakiya et al (submitted) conducted experimental stocking of farmed eels in four rivers with various densities of wild eels. It was found that the growth rates of farmed eels were greater in rivers with lower wild eel density, but significant differences in survival rate were not detected (Wakiya et al ., submitted). Although a greater understanding of the interactions between wild and stocked farmed eels is needed, it appears that stocking farmed eels in areas with abundant wild eels would not be the most effective strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the possible effects of wild eels on farmed eels that were stocked in natural water bodies, Wakiya et al (submitted) conducted experimental stocking of farmed eels in four rivers with various densities of wild eels. It was found that the growth rates of farmed eels were greater in rivers with lower wild eel density, but significant differences in survival rate were not detected (Wakiya et al ., submitted). Although a greater understanding of the interactions between wild and stocked farmed eels is needed, it appears that stocking farmed eels in areas with abundant wild eels would not be the most effective strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This model provides dynamic description about the strength of density dependence with respect to environmental variations. In addition, our model embodies the density dependence of a combination of biological traits, including growth, fecundity and post‐recruitment mortality, which have been demonstrated separately by previous studies (Achord et al, 2003; Crozier et al, 2010; Raid et al, 2010; Stenevik et al, 2022; Wakiya et al, 2022). The density‐dependent effects presented by our mechanistic model were comparable to relevant field observations.…”
Section: Discussionmentioning
confidence: 95%